The Dader Method in pharmaceutical attention of hypertensive patients at Pontal do Araguaia/MT, Brazil - Maria Fernanda Spegiorin Sala Brune; Ellen Eliane Ferreira; Carlos Kusano Bucalen Ferrari (O Mundo da Saúde)
Hypertension has a high prevalence and low control rates, being considered one of the worst public health challenges. In this context, pharmaceutical care has been established as a new clinical practice for the pharmacist. The objective of this study was to investigate the control of hypertension in adults according to the Dader Method of Pharmacotherapy Monitoring. The Dader Method of Pharmacotherapy Monitoring was applied to 25 patients with continued use of antihypertensive medications, registered in the “Unidade Básica de Saúde” (Basic Health Unit) at Pontal do Araguaia-MT, Brazil, during three months. The analysis was done through descriptive statistics and Student’s t test for paired samples. Among the data obtained, it was found that 100% of the patients presented drug related problems, requiring 133 pharmaceutical interventions aimed at addressing these problems. The most common PRM was not using the medicine needed by the patient. At baseline, 40% of patients had uncontrolled hypertension despite prescribed treatment. After the pharmaceutical interventions, all patients had a reduction in blood pressure, and only 8% did not reach the normal blood pressure levels. The application of Dader Method resulted in significant improvement in blood pressure of patients throughout the pharmacotherapy monitoring, confirming its importance in the outpatient management of hypertension.